India Transport Report Volume II Main Report Part II - Planning Commission (Planning Commission, 2013)
The high growth rate of new vehicle registrations is expected to continue, at least through the remainder of this decade. The continued growth of the transport sector may be vital for further economic development, but it has exacerbated India’s critical air pollution problem: vehicular emissions. Hydrocarbons (HC), carbon monoxide (CO), oxides of nitrogen (NOX), particulate matter (PM), and carbon dioxide (CO2) are a critical issue that has to be tackled on a wartime footing.
Moving India To 2032
National Transport Development Policy Committee